Kajian Tentang Pengaruh Persepsi Dukungan Organisasi terhadap Perilaku Kerja Karyawan Pasca Restrukturisasi: Studi pada Karyawan Perusahaan Teknologi Berbasis Digital - Maulani Y., Luthvia Nur; Pusparini, Elok Savitri (Universitas Proklamasi 45, 2025)
The development of digital-based technology has triggered the phenomenon of Tech Winter, leading to layoffs and increasing job insecurity among surviving employees. This study aims to analyze the effect of perceived organizational support (POS) on job insecurity and its impact on the task performance and innovative behavior of layoff survivors. The study also explores how affective commitment acts as a mediator, while financial job dependence and organizational cynicism serve as moderators in the relationship between job insecurity and work performance, as well as innovative behavior among layoff survivors in digital technology companies. This research employs the Partial Least Squares Structural Equation Modelling (PLS-SEM) method to analyze the relationships between variables. The sample consists of 262 respondents who are layoff survivors working in digital technology companies in Indonesia. The results show that perceived organizational support (POS) has a significant effect in reducing job insecurity, which in turn improves task performance and innovative behavior. Affective commitment serves as a significant mediator, while financial job dependence and organizational cynicism moderate the impact of job insecurity on work outcomes. These findings highlight the importance of organizational support in mitigating job insecurity for employees after a layoff.